2000
DOI: 10.1067/mhn.2000.105254
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Children with Obstructive Sleep Apnea

Abstract: The caregivers of 61 eligible children (6 months to 12 years old) completed a 20-item (OSA-20) health-related quality-of-life survey after polysomnography was performed to psychometrically validate the OSA-20. Excellent test-retest reliability was obtained for the individual survey items (R>0.74). Construct validity was shown by significant correlation of the mean survey score with the respiratory distress index (R = 0.43) and adenoid size (R = 0.43). Two items with poor validity were dropped, reducing the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(164 citation statements)
references
References 9 publications
3
142
0
Order By: Relevance
“…The gold standard for the assesment of the presence and severity of obstructive symptoms is polysomnographic study [32]. However, it was reported that OSA-18 is a practical and reliable method and has shown validity for detecting change and evaluating quality of life after adenotonsillectomy in children with OSA [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gold standard for the assesment of the presence and severity of obstructive symptoms is polysomnographic study [32]. However, it was reported that OSA-18 is a practical and reliable method and has shown validity for detecting change and evaluating quality of life after adenotonsillectomy in children with OSA [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-known that the OSA-18 have a high level of test-retest reliability, validity, and responsiveness in OSA syndrome and has also shown validity for detecting change and evaluating quality of life after adenotonsillectomy in children with OSA syndrome [17][18][19]. This instrument, which contains an 18-item quality of life survey, was filled out by parents on a 7-point scale from ''none'' to ''all of the time''.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical information regarding patient history was reported by a parent or responsible guardian. An 18-item quality of life questionnaire (OSA-18), specifically designed for the pediatric population, was used to identify OSA risk factors and document the relevant history [13]. After the initial clinical assessment, 20 children completed AR measurements and overnightattended PSG.…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…Daytime somnolence, fatigue, headaches, poor appetite, short attention span are caused by constant hypoxia and frequent arousals [14,16,19]. Moreover respiratory disorders and frequent infections of upper respiratory tract appear in children with sleep-disordered breathing [1,3,5,6,10]. Sleep apnea may lead to failure to thrive and to physical and mental delay in development, including cognitive disturbances [12,20].…”
Section: Introductionmentioning
confidence: 99%